Medico-social and legal aspects of childcare - Tytuła, Andrzej; Jasztal-Kniażuk, Anita; Błaszkiewicz, Paweł Szczepan; Kulbaka, Ewa; Bartosik, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Childcare is an multi-faceted problem that should be considered depending not only on family situation of a particular child, but also on his social and health conditions. Among the selected aspects of childcare, awareness of which constitutes an integral element of practical nurse, the medical, social and legal aspects should be enumerated. The nurses, as a professionals perform their profession according to the Polish Act of 15 July 2011 concerning professions of nurses and midwives. They undertake many activities to ensure an adequate quality of services and bear full responsibility for implementation of services that constitute a part of their professional competence. For that reason, the professional activities of nurses are constantly evaluated in accordance with standards which are incorporated in deontological and ethical codes and legal acts regulating nurses’ professional practice. This evaluation is always connected with a social resonance and the decisions made by the nurses have specific consequences in terms of the legal, criminal, civil, material, professional and ethical liability. The aim of this study is to emphasise the fact that the pursuit of the occupation of nurse in the aspect of childcare must be related to a full professional awareness of medico-social and legal aspects of childcare, regardless of the form of the professional activity or the type and place of provided health services. These aspects of the childcare were presented by the example of the various fields such as: control of pediculosis prevalence, protective vaccination, the role of the primary care nurses in treatment of homebound children prescribed antibiotic therapy via injections, which became subjects of heated debates among medical community representatives, social movements and mass-media. For the purpose of this investigation the legal acts, the scientific literature and our own experience in the field of contribution of the nurses in the implementation of health services based on data from District Chamber of Nurses and Midwives in Lublin have been analyzed.